Rola środków unijnych w stymulowaniu procesów rozwojowych w małych i średnich przedsiębiorstwach w Polsce na przykładzie wybranych programów operacyjnych - Brojak-Trzaskowska, Małgorzata (The Role of EU Funds to Stimulate Development Processes in Small- and Medium-Sized Enterprises in Poland, 2009)
The article is on selected issues of external funding for the development of small- and medium-sized enterprises in Poland, with particular emphasis on operational programmes. Due to the limited framework of volumetric studies, the considerations about the development processes were focused on the issue of activation of innovative activity, as well as the development of human resources. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 534-540